Knowledge and Participation of Barranquilla’s Citizens in the Colombian Stock Market - León, Guillén; Afcha Chávez, Sergio Moisés (CENTRUM Publishing, 2015)
This paper empirically examines the level of awareness and participation of citizens of Barranquilla in Colombia's stock market. To do this, we surveyed 800 individuals distributed in five locations in the city. Using a logit model type factors influencing the level of market knowledge of small investors as well as the variables that influence the probability of investment are estimated. The results show that the income range is the variable with the greatest influence on the level of knowledge and investment in the stock market. Finally, it is confirmed that this is a market with very specific characteristics in which, in most cases, enter those with a full knowledge of investments they put in.
Keywords: Barranquilla; Citizens; Market knowledge; Financial culture; http://purl.org/pe-repo/ocde/ford#5.02.04